Portugal : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The staff report for the 2005 Article IV Consultation on Portugal highlights economic developments and outlook. Private consumption has proven resilient, reflecting low interest rates and lengthening tenors on bank lending, while investment and export growth remained weak. Executive Directors concurred that in an unfavorable context marked by large fiscal and external imbalances, slow growth, and a weak competitive position, the challenge confronting the Portuguese government is to create the conditions to restart Portugal's per capita income convergence toward the euro area average as soon as possible.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet